Lipid-Based Nutrient Supplements During Pregnancy and Lactation Did Not Affect Human Milk Oligosaccharides and Bioactive Proteins in a Randomized Trial. Issue 10 (9th August 2017) - Jorgensen, Josh M; Arnold, Charles; Ashorn, Per; Ashorn, Ulla; Chaima, David; Cheung, Yin Bun; Davis, Jasmine CC; Fan, Yue-Mei; Goonatilleke, Elisha; Kortekangas, Emma; Kumwenda, Chiza; Lebrilla, Carlito B; et al.
Abstract: Background: Human milk oligosaccharides (HMOs) and bioactive proteins are beneficial to infant health. Recent evidence suggests that maternal nutrition may affect the amount of HMOs and proteins in breast milk; however, the effect of nutrient supplementation on HMOs and bioactive proteins has not yet been well studied. Objective: We aimed to determine whether lipid-based nutrient supplements (LNSs) affect milk bioactive protein and HMO concentrations at 6 mo postpartum in women in rural Malawi. These are secondary outcomes of a previously published randomized controlled trial. Methods: Women were randomly assigned to consume either an iron and folic acid capsule (IFA) daily from ≤20 wk gestation until delivery, followed by placebo daily from delivery to 6 mo postpartum, or a multiple micronutrient (MMN) capsule or LNS daily from ≤20 wk gestation to 6 mo postpartum. Breast milk concentrations of total HMOs, sialylated HMOs, fucosylated HMOs, lactoferrin, lactalbumin, lysozymes, antitrypsin, immunoglobulin A, and osteopontin were analyzed at 6 mo postpartum ( n = 647). Between-group differences in concentrations and in proportions of women classified as having low concentrations were tested. Results: HMO and bioactive protein concentrations did not differ between groups ( P > 0.10 for all comparisons). At 6 mo postpartum, the proportions of women with low HMOs or bioactive proteins were not different between groups except for osteopontin. A lower proportion of women in the IFA group had low osteopontin compared with the LNS group after adjusting for covariates (OR: 0.5; 95% CI: 0.3, 0.9; P = 0.016). Conclusion: The study findings do not support the hypothesis that supplementation with an LNS or MMN capsule during pregnancy and postpartum would increase HMO or bioactive milk proteins at 6 mo postpartum among Malawian women. This trial was registered at clinicaltrials.gov as NCT01239693.